Existence of global attractors for impulsive dynamical systems - Kapustyan, O. V.; Kapustyan, O. V.; Perestyuk, M. O. (Reports of the National Academy of Sciences of Ukraine, 2015)
The existence of global attractors for impulsive dynamical systems, which have trajectories with infinite number of impulsive perturbations, is investigated. We have proved the existence of a global attractor for a parabolic equation with nonlinear perturbation.